Arthroscopic Knotless Double-Bundle Inferior Glenohumeral Ligament Reconstruction for Static Inferior Shoulder Subluxation - Abdul-ilah Hachem, M.D.; Gonzalo Barraza, M.D.; Fernando Alvarado, M.D.; Xavier Rius, M.D.; Antonio Arenas-Miquelez, M.D. (Arthroscopy Techniques)
Inferior subluxation of the humeral head may lead to ongoing shoulder instability after attempted stabilization procedures. This implies a challenging situation for the surgeon to address, and the cause is unclear. However, ligament insufficiency of the rotator interval complex and abnormal muscle activation of the rotator cuff and deltoid are common contributing factors. Currently, there is no fair solution for these patients, and they end up being treated with either glenohumeral arthrodesis or reverse shoulder arthroplasty. However, reconstruction of the inferior glenohumeral ligament may reinforce the hammock formed by the native inferior glenohumeral ligament and could potentially prevent inferior subluxation and preserve the shoulder joint. We describe an all-arthroscopic knotless double-bundle anatomic reconstruction of the inferior glenohumeral ligament using a semitendinosus allograft for patients with inferior subluxation of the humeral head who have already undergone unsuccessful stabilization surgeries.